Remote underground cable fault detector (part 2) - Nur Ain Muhammad (Nanyang Technological University, 2023)
This report focuses on the steps taken on designing a compact and portable hardware frame for the Remote Underground Cable Fault Detector. In the context of this project, Nanyang Technological University (NTU) has collaborated with Singapore Power (SP) to design a hardware frame using Solidworks to house the audio detecting scanner when being used on the roads. The hardware was designed to be inexpensive and simple to operate. The prototype was fabricated by using a range of tools such as laser cutting, bench grinder machine and turning machines. Subsequently, individual components were assembled using bolts and nuts. This process engages and incorporates multiple disciplines such as Design Thinking, Concept Evaluation and Selection and mechanical machines. Afterwards, the electrical process was designed where it uses Arduino Uno with L239D Motor Shield to control four DC motors and one servo motor to control the wheels as well as the replica of the digiPHONE+ sensor respectively. This process comprises multiple competencies such as Arduino programming, soldering as well as performing mathematical calculations for the circuit. The final prototype is the integration of the mechanical and electrical components where results and challenges are mentioned in this report, which will all be explained in detail below.